Identification and analysis of the controlled object parameters on the ergatic education system - Шибицкая, Н. Н. (Proceedings of National Aviation University (archive), 2000)
Proposed is the technique of object parameters identification in the ergatic education system. Analyzed are information processes in the system depending on the parameters of the education subject model. Investigated is the influence of the number of repetitions on the process of information assimilation and conservation in the operator memory